2005
DOI: 10.1523/jneurosci.5298-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Metabotropic Glutamate Receptors Contribute to Habituation of a Simple Odor-Evoked Behavior

Abstract: Defining the circuits that are involved in production and cessation of specific behaviors is an ultimate goal of neuroscience. Short-term behavioral habituation is the response decrement observed in many behaviors that occurs during repeated presentation of nonreinforced stimuli. Within a number of invertebrate models of short-term behavioral habituation, depression of a defined synapse has been implicated as the mechanism. However, the synaptic mechanisms of short-term behavioral habituation have not been ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 27 publications
1
50
0
Order By: Relevance
“…Post hoc Fisher tests revealed that time points after 10 s were significantly different between CPPG and aCSF (P < 0.05). The present results demonstrate that a form of activity-dependent synaptic depression recently found to be involved in both cortical and behavioral olfactory sensory gating [2,3] is functional by at least the first postnatal week in the rat aPCX and shares a common mGluR mechanism. aPCX pyramidal cell dendritic branching [18], aPCX cell survival [10] and synaptic and membrane properties of piriform pyramidal cells [1,5] are all odor experience dependent in the rat.…”
supporting
confidence: 60%
See 1 more Smart Citation
“…Post hoc Fisher tests revealed that time points after 10 s were significantly different between CPPG and aCSF (P < 0.05). The present results demonstrate that a form of activity-dependent synaptic depression recently found to be involved in both cortical and behavioral olfactory sensory gating [2,3] is functional by at least the first postnatal week in the rat aPCX and shares a common mGluR mechanism. aPCX pyramidal cell dendritic branching [18], aPCX cell survival [10] and synaptic and membrane properties of piriform pyramidal cells [1,5] are all odor experience dependent in the rat.…”
supporting
confidence: 60%
“…The mGluR-mediated mechanism underlies both piriform cortical and behavioral short-term adaptation (sensory gating) to odors. Specifically, the infusion of the group II/III mGluR antagonist (RS)-α-Cyclopropyl-4-phosphonophenylglycine (CPPG) into the anterior piriform cortex (aPCX) blocks both cortical and behavioral odor adaptation, without disrupting normal odor responses [2,3]. CPPG antagonizes pre-synaptic group III mGluRs on mitral/tufted cell axons projecting to the piriform cortex and blocks activity-dependent intermediate duration synaptic depression at this synapse.…”
mentioning
confidence: 99%
“…In the thalamus, for example, mGluRs are coupled to presynaptic release from GABA-containing interneurons, and strongly modulate feedforward information flow to higher cortical areas (Cox and Sherman, 2000;Govindaiah and Cox, 2004). Similarly, in the main olfactory system, a presynaptic group II mGluR has been shown to be critical for habituation of the odorinduced heart-rate orienting response (Best et al, 2005). The AOB provides perhaps the most tractable example of a feedforward system in which information flow is controlled by mGluRs.…”
Section: Discussionmentioning
confidence: 99%
“…(Isaacson and Strowbridge, 1998;Schoppa et al, 1998;Taniguchi and Kaba, 2001;Urban, 2002). This relatively simple relay-like relationship between the AOB and downstream structures motivates the hypothesis that RI serves a sensory "gating" function (Brennan et al, 1990;Kaba et al, 1994;Brennan and Keverne, 1997;Best et al, 2005). Behavioral and physiological experiments support this notion, as changes in the strength of RI are thought to underlie specific forms of olfactory learning (Hayashi et al, 1993;Kaba et al, 1994;Brennan and Keverne, 1997).…”
Section: Introductionmentioning
confidence: 86%
“…Our data show CORT shifts learning-induced changes between the anterior and posterior piriform cortex, suggesting input to the amygdala is altered by CORT. In adults, both the anterior and posterior piriform cortex appear to be involved in learning, but the posterior piriform cortex may be more strongly implicated in associative memory processes (Hasselmo and Barkai, 1995;Litaudon et al, 1997;Barkai and Sahar, 2001;Haberly, 2001;Mouly et al, 2001;Tronel and Sara, 2002;Best et al, 2004;Sevelinges et al, 2004;Wilson et al, 2004).…”
Section: Adult and Infant Circuits For Odor-shock Conditioningmentioning
confidence: 99%